A New and Efficient Lattice-Based Online/Offline Signature From Perspective of Abort. (31st May 2021) - Zhang, Pingyuan; Jiang, Han; Zheng, Zhihua; Wang, Hao; Xu, Qiuliang
Abstract: Lattice-based online/offline signature is attractive for the merit of resisting quantum attacks besides the short online response time. Prior to this work, the hash-sign-switch paradigm lattice-based online/offline signatures usually increase the length of each signature, and the Fiat–Shamir candidates are highly inefficient due to multiple aborts in online signing phase. In this work we mainly address its efficient issue and propose a new paradigm of its construction in the perspective of abort. In this paradigm, one tries to remove one or more aborts from online to offline signing phase by Γ -transformation. Specifically, this work proposes an efficient lattice-based online/offline signature scheme with fewer online aborts and thus allows the signer to obtain a valid signature by fewer online repetitions. Through this way, the resulting scheme can reduce much online signing time with the same signature size. The performance evaluation shows that our scheme is efficient and practical.